PENGARUH METODE PJBL TERHADAP MINAT BELAJAR DAN KREATIVITAS SISWA PADA PEMBELAJARAN TIK DI SMPIT AL-AKHYAR KELAS VII: English - Udin, Fitrah (JURNAL KEILMUAN TEKNOLOGI DAN PENDIDIKAN TERPADU, 2025)
This study aims to determine the effect of the Project Based Learning (PjBL) method on students’ learning interest and creativity in ICT learning for seventh-grade students at SMPIT Al-Akhyar. The background of this research is the low level of student interest and creativity caused by monotonous and teacher-centered learning. The study employed a quantitative approach with a quasi-experimental design. The subjects consisted of 48 students divided into an experimental class and a control class using a total sampling technique. The instruments were questionnaires on learning interest and creativity that had been tested for validity and reliability, while the data were analyzed using a t-test with the help of SPSS version 26.The results show that the implementation of PjBL had a significant effect on increasing students’ learning interest and creativity. Students in the experimental class were more enthusiastic, active, and able to produce creative works that reflected deeper understanding. PjBL also encouraged students to collaborate, think critically, and engage in meaningful and contextual learning experiences.Practically, this research implies that teachers can use PjBL as an alternative strategy for enjoyable and effective ICT learning. Socially, PjBL fosters 21st-century skills such as collaboration, communication, and creativity that are beneficial for social life. The originality of this study lies in the application of PjBL in ICT subjects at the junior high school level, which has rarely been investigated, with a dual focus on both learning interest and student creativity.